1996
DOI: 10.1002/star.19960480106
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Phase Transition of Native, Cross‐linked, and Hydroxypropylated Rice Starches

Abstract: Kinetics of the phase transition of native and chemically modified rice starches have been investigated by using differential scanning calorimetry (DSC) after isothermal treatment. At the experimental conditions, the phase transition of these starches followed pseudo-first order kinetics. The kinetic order was not affected by the two chemical modifications used, hydroxypropylation and cross-linking, while the rate constants were altered. From the Arrhenius plot, peak temperature (T,) from DSC thermogram appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
0
25
0
2
Order By: Relevance
“…(compared to native starch) were also observed for hydroxypropytated rice starch by Yeh & Yeh (1993) and Yeh & Jeng-Yune (1996). Butler et al (1986) reported that swelling power (SP) of buffalo gourd root starch was unaltered on hydroxypropylation (MS 0.003 -0.06).…”
Section: Hydroxypropylatlonmentioning
confidence: 62%
See 1 more Smart Citation
“…(compared to native starch) were also observed for hydroxypropytated rice starch by Yeh & Yeh (1993) and Yeh & Jeng-Yune (1996). Butler et al (1986) reported that swelling power (SP) of buffalo gourd root starch was unaltered on hydroxypropylation (MS 0.003 -0.06).…”
Section: Hydroxypropylatlonmentioning
confidence: 62%
“…Hydroxypropylation was shown to alter physicochemical properties of starches (Wootton & Manatsathit, 1984;Butler et a/., 1986;Seow & Thevamalar, 1993;Yeh & Yeh, 1993;Yeh & Jeng-Yune, 1996). Wootton & Manatsathit (1984) showed (using eSC) that increase in MS of hydroxypropylated maize starches (MS 0-0.27) decreased gelatinization enthalpy (6H), onset (To) and peak (To) temperatures, whereas the gelatinization temperature range (Tc -To) remained unaffected.…”
Section: Hydroxypropylatlonmentioning
confidence: 99%
“…Yeh and Li 30 reported that crosslinking increases the heat of gelatinization of rice starch. The crosslinked wheat starches were reported to have virtually changed the onset (T 0 ) and peak (T p ) temperatures values compared with unmodified starch, (T p ) was slightly increased.…”
Section: Resultsmentioning
confidence: 99%
“…During gelatinization the starch pastes comprise swollen granules suspended in hot water in which molecules of amylose (considered responsible for most of the thickening) are dispersed. The increase in viscosity of a heated paste was attributed (Hsu, Lu, & Huang, 2000;Yeh & Li, 1996a, 1996b to release of an exudate (predominantly amylose) and folding (deformation) of the swollen starch granules. The PV results suggest that the addition of fatty acids, particularly the saturated fatty acid (C18:0) effectively restrained the starch granule from hydration and swelling behaviors during gelatinization.…”
Section: Effect Of Fatty Acids On Starch Pasting Propertiesmentioning
confidence: 97%